Western African scenarios for resource access - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Land Tenure and Resource Access in West Africa: Issues and Opportunities for the next Twenty-five Years. IIED Drylands. 1999. 43 pp. ISBN 1899825312. £7.50 12.30 (free to non-OECD) IIED Bookshop 3 Endsleigh Street, London WC1H 0DD, UK. (Quot